Governance, Accountability and Performance in Agricultural Research and Innovation - Gijsbers, Govert (International Service for National Agricultural Research, 1999)
In ISNAR's strategic plan (1998-2002) governance has been identified as one of four new thrust areas to receive special attention. Although the topic of governance as such is new for ISNAR, it builds on earlier ISNAR work on organization and structure, system development, and on strategic planning and the design and management of linkages. In recent years, much work on governance and related issues has been carried out in a variety of disciplines by researchers and practitioners in universities and research organizations. ISNAR can benefit by relating its own experience and expertise in research management and strategy to the experiences and insights developed by other organizations that deal with complex institutional arrangements involving public, private and voluntary sector organizations. The concept of governance will allow ISNAR to bring together a number of critical elements that relate to important questions of how organizations are steered and supervised, how they interact with their environments and how they engage in inter-organizational arrangements.